Prijevodi poezije Hafiza Širazija na zapadnom Balkanu - Drkić, Munir (2021)
Predmet ovoga članka jesu dosad objavljeni prijevodi poezije klasičnog perzijskog pjesnika Hafiza Širazija (XIV st.) na geografskom prostor zapadnoga Balkana. Istraživanje pripada oblasti studija prevođenja, s posebnim naglaskom na ponovljene i posredne prijevode. Prvi prijevod Hafiza iz pera Jovana Jovanovića Zmaja objavljen je 1861. godine i predstavlja najraniji prijevod jednog perzijskog teksta na južnoslavenske jezike. Ukupno devet prijevoda objavljivanih u Bosni i Hercegovini, Srbiji i Hrvatskoj podijeljeno je u dva kraća perioda: prvi krajem XIX i početkom XX stoljeća i drugi početkom XXI stoljeća. Svaki od dva različita povijesna trenutka, omeđena dominatnim kulturnim narativima, donio je novo čitanje, novu vrijednost Hafizovoj poeziji u ciljnoj kulturi. U prvom je periodu Hafiz Širazi predstavljen kao hedonist i vinopija, dok su prevoditelji s početka XXI stoljeća prepoznavali dublji smisao i mistički, odnosno gnostički sadržaj u njegovoj poeziji. Prema tome, svi su prijevodi imali snažan evaluativni aspekt. Svega su dva prijevoda integralni, a ostali su izbori ili adaptacije pojedinih dijelova izvornika. Prevoditelji su prevodili s perzijskog, njemačkog i engleskog jezika. Zahvaljujući raznovrsnim pristupima prevoditeljâ, poezija Hafiza Širazija očuvala je i učvrstila kanonski status među starim i novim recipijentima na zapadnom Balkanu što ga je još u osmanskom periodu stekla među obrazovanom muslimanskom elitom.
This paper investigates the translations of the poetry of the classical Persian poet Hafiz Shirazi (14th century) published so far in the Western Balkans. The research belongs to the field of translation studies, with particular emphasis on retranslations and relay translations. The first translation of Hafiz by Jovan Jovanović Zmaj published in 1861 was at the same time the earliest translation of a Persian text in the Western Balkans. I classify the past nine translations published in Bosnia and Herzegovina, Serbia, and Croatia into two periods. The first period was between the 1860s and 1920s, and the second took place at the beginning of the 21st century. The main conclusion is that each of the two historical periods, bounded by dominant cultural narratives, ushered in a new spirit, and added a new value to Hafiz"s poetry in the target culture. At the turn of the 19th and 20th centuries, Hafiz Shirazi was presented as a hedonistic poet and winebibber in the Western Balkans. However, at the beginning of the 21st century, translators sought a more profound meaning and mystical content in this Persian lyricist"s poetry. Therefore, one can conclude that all the translations of his poetry have an evaluative aspect. In addition, only two translations are integral, and the rest are selections or adaptations. The translators used the Persian source text or various German and English translations as their basis. Owing to such diverse approaches, the poetry of Hafiz Shirazi has preserved and further bolstered its canonical status among the old and new recipients in the Western Balkans that it had acquired in the Ottoman period among the educated Muslim elite.
Bibliografske bilješke uz tekst ; bibliografija: str. 555-557 ; izvori: str. 554.
Sažetak ; Summary.
Keywords: Perzijska književnost -- Prijevodi; Širazi, Hafiz; Zapadni Balkan